TOWARDS AN ASSESSMENT OF INTERCULTURAL COMPETENCE IN LANGUAGE CLASSES: CHALLENGES AND ISSUES FOR FLE TEACHERS IN SECONDARY EDUCATION IN ALGERIA - Sabah BEDDIAF; Nouhad TIGANI (Analele Universităţii din Craiova. Psihologie, Pedagogie)
This study seeks to critically examine and reevaluate the practices associated with assessing intercultural competence in French as a Foreign Language (FLE) classroom within the Algerian educational context. The primary focus is to address specific deficiencies in the evaluation process, particularly those arising from the inherently transdisciplinary nature of intercultural competence. Special attention is given to the application of the culture assimilator method, employed as a tool to facilitate a more objective assessment of intercultural competence in Algerian schools. By doing so, the study aims to reintegrate interculturality into language instruction and to conceptualize FLE learning as a meaningful avenue for fostering an understanding of otherness.